2017
DOI: 10.1101/163188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The WYL domain of the PIF1 helicase from the thermophilic bacteriumThermotoga elfiiis an accessory single-stranded DNA binding module

Abstract: PIF1 family helicases are conserved from bacteria to man. With the exception of the well-studied yeast PIF1 helicases (e.g., ScPif1 and ScRrm3), however, very little is known about how these enzymes help maintain genome stability. Indeed, we lack a basic understanding of the protein domains found N-and C-terminal to the characteristic central PIF1 helicase domain in these proteins. Here, using chimeric constructs, we show that the ScPif1 and ScRrm3 helicase domains are interchangeable and that the N-terminus o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Such a potential factor may thus well be an RNA molecule or, in a broader context, a nucleic-acid or nucleic acid derivative, relaying the signal of DNA damage to PafBC by recognition at the WYL and/or WCX domains. In fact, the WYL domain of PIF1 helicase from Thermotoga elfii was shown to bind singlestranded DNA, thereby stimulating helicase activity (Andis et al, 2018). Binding of single-stranded DNA may be conceivable for the WYL domain proteins of class J of our computational analysis, which are also associated with a helicase domain.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Such a potential factor may thus well be an RNA molecule or, in a broader context, a nucleic-acid or nucleic acid derivative, relaying the signal of DNA damage to PafBC by recognition at the WYL and/or WCX domains. In fact, the WYL domain of PIF1 helicase from Thermotoga elfii was shown to bind singlestranded DNA, thereby stimulating helicase activity (Andis et al, 2018). Binding of single-stranded DNA may be conceivable for the WYL domain proteins of class J of our computational analysis, which are also associated with a helicase domain.…”
Section: Discussionmentioning
confidence: 84%
“…However, understanding and experimentation concerning the regulatory mechanism of PafBC was largely hampered by a lack of knowledge about its molecular structure. This limitation has manifested also in other studies concerning WYL domain-containing proteins (Andis et al, 2018;Hein et al, 2013;Modell et al, 2014;Yan et al, 2018). Our computational analysis showed that roughly 90% of all WYL domain-containing proteins possess an N-terminal HTH domain suggesting that these are transcriptional regulators (Figure 6a).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We previously demonstrated that the non-helicase CTD (a predicted WYL domain [32]) of the bacterial TePif1 helicase is an accessory ssDNA binding domain [12]. This WYL domain impacts both ATP hydrolysis and DNA unwinding, coupling the two to regulate the biochemistry of the helicase.…”
Section: Discussionmentioning
confidence: 99%
“…Among the two Saccharomyces cerevisiae PIF1 family helicases, Rrm3 and Pif1, it is known that the NTD of Rrm3 is essential for its functions in vivo because truncation of the Rrm3 NTD phenocopies the null allele [11]. However, the Rrm3 NTD can be fused to the S. cerevisiae Pif1 helicase domain or the helicase domain of bacterial Pif1 proteins, and these chimeras can rescue the synthetic lethality of cells lacking Rrm3 and, for instance, the gene encoding the Srs2 helicase [12]. Thus, in this experimental set up, the PIF1 helicase domains are generic and interchangeable motor modules, while the Rrm3 NTD is vital for genome integrity.…”
Section: Introductionmentioning
confidence: 99%